Friction and Wear: Methodologies for Design and Control - Straffelini, Giovanni (Springer, 2015)
is book introduces the basic concepts of contact mechanics, friction, lubrication, and wear mechanisms, providing simplified analytical relationships that are useful for quantitative assessments. Subsequently, an overview on the main wear processes is provided, and guidelines on the most suitable design solutions for each specific application are outlined. The final part of the text is devoted to a description of the main materials and surface treatments specifically developed for tribological applications and to the presentation of tribological systems of particular engineering relevance. The text is up to date with the latest developments in the field of tribology and provides a theoretical framework to explain friction and wear problems, together with practical tools for their resolution. The text is intended for students on Engineering courses (both bachelor and master degrees) who must develop a sound understanding of friction, wear, lubrication, and surface engineering, and for technicians or professionals who need to solve tribological problems in their work.